FRI0054 A novel pharmacological action of MTX through circadian clock genes in RA fibroblast-like synovial cells. (15th June 2017) - Suzuki, K; Yoshida, K; Hashimoto, T; Kaneshiro, K; Nakai, A; Hashimoto, N; Kawasaki, Y; Shibanuma, N; Nakagawa, N; Sakai, Y; Hashiramoto, A
Abstract : Background: Methotrexate inhibits the proliferation of RA fibroblast-like synovial cells (RA-FLS) by folate anti-metabolism. We previously reported that disruptions of circadian clock genes were involved in the pathogenesis of inflammatory arthritis (1, 2). Objectives: To explore pharmacological effects of MTX on circadian clock genes of RA-FLS. Methods: Under treatments of MTX on RA-FLS, cell viabilities were determined by WST-8 assay, expressions of circadian clock genes ( Clock, Bmal1, Cry1 and Per2 ), circadian transcriptional factor PAR bZip ( Dbp, Tef and Hlf ), and pro-apoptotic Bcl-2 interacting killer ( BIK ) were examined by real time PCR, and expressions of PER2 and CYTOCHROME C were examined by western blotting. The expressions of PER2, BIK, CYTOCHROME C and morphological changes of the nucleus were observed by fluorescent immunostaining. RA-FLS were transfected with Per2 and BIK siRNAs and successively treated with MTX to determine cell viabilities by WST-8 assay. Results: MTX (1, 10 nM) treatment significantly decreased the cell viabilities. MTX (10nM) have increased mRNA expression of Per2, Dbp, Tef, Hlf, and BIK, and protein expressions of PER2 and CYTOCHROME C, as well. In fluorescent observations, PER2, BIK, and CYTOCHROME C were increased in apoptotic cells. Cytotoxicity of MTX was attenuated by knockdowns of Per2 or BIK in RA-FLS. Conclusions: The transcriptional factor PAR bZip binds to the D-box elements of Per2 and BIK promoters (3, 4). Here, we propose a novel action of MTX that up-regulates the expressions of Per2 and BIK via PAR bZip to induce apoptosis in RA-FLS. References: Hashiramoto A, J Immunol. 2010 Feb 1;184(3):1560–5. Hand LE, FASEB J. 2016 Nov;30(11):3759–3770. Yoshida K, Scand J Rheumatol. 2013;42(4):276–80. Ritchie A, Cell Death Differ. 2009 Jun;16(6):838–46. Disclosure of Interest: None declared